(untitled) (Journal of Global Humanities and Social Sciences, 2024)
With the arrival of the "Internet Plus" era, Internet technology is profoundly affecting the preschool education profession. This paper discusses the current situation of preschool education professional career development and the problems it faces under the background of "Internet Plus", and puts forward four innovative paths. These include broadening career development channels to enhance job diversity; promoting distance education and online training to expand career learning channels; creating an online-offline integrated education model to enrich career choices; and strengthening the integration and sharing of industry resources to promote career co-development, aiming to promote the vocational skills upgrading and diversified development of preschool education practitioners. By strengthening the integration and sharing of industry resources, breaking down the barriers between institutions and employers, promoting school-enterprise and school-local co-operation, and constructing a complete education ecosystem, preschool education practitioners can not only better adapt to the market demand, but also realise the sustainable development of their careers with the help of Internet technology.